Political Ideology and the Production of Architectural Theories in Mao's China (1949–1976). Issue 1 (14th December 2018) - Song, Ke
Abstract : This paper reveals a missing thread in the global historiography of architectural theory by scrutinizing the relationship between political ideology and architectural discourse in Mao's China (1949–76). Several critical moments in this era, during which new theories or concepts emerged, deserve close study: 1) the National Style in 1954; 2) the official design principle, 'appropriateness, economy, and if possible, beauty' in 1955; 3) the Socialist New Style in 1959; 4) the Design Revolution in 1964; and 5) the 'new architecture' in 1973. The political context and the role of state ideology are discussed with regard to the relevant texts, buildings, architects and design institutes. Discussion focuses on the mode of theoretical production in the Mao era, which is summarized as a relation between 'container' and 'content'. The broad and abstract theories of the time are conceptual containers that failed to define specific contents. Architectural autonomy continued to exist in the form of knowledge accumulation, especially the absorption of modernism, even though state ideology and political movements dominated architectural discourse.